Memory, ageing and Alzheimer's disease: the case for Malaysia - Dzulkifli, Mariam Adawiah (Pearson, 2012)
The chapter starts with a section on ageing and memory. It aims to provide some answers as to why increased age is commonly associated with a decline in cognitive ability, especially memory performance. A section on AD is first presented, followed by a discussion of the potential of newly developed of non-biological explanations for the disease. The chapter concludes with some recommendations to approach ageing by providing more emphasis on health promotion and disease prevention in elder persons.